George Fox's 'Book of Miracles' - Fox, George (Cambridge library collection. Religion, 1948)
George Fox (1624–91), founder of The Religious Society of Friends (or Quakers), was well known during his lifetime as a healer and worker of miracles. He wrote prolifically of how he used God's power to effect over one hundred and fifty cures, of both physical disease or injury and mental or psychological problems. This work was critical to spreading the word about Quakerism in its early years. Many of Fox's papers were lost after his death, but from the clues and fragments that remained, and a contemporary index of his works, Henry Cadbury (1883–1974) was able to create this book, published in 1948. The preface make clear that this was not intended as a work of critical analysis, though the findings are annotated with historical and documentary detail. The editor's devotion to his task is testament to the historical and spiritual significance of Fox's contribution to Quakerism